Compliance in taking medication for hypertension patients listed at Healthy Indonesia Program with a Family Approach - Merry Tiyas Anggraini; Aisyah Lahdji; Hema Dewi Anggraheny (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACTCompliance is the main factor in determining the success of treatment of hypertension and is needed for controlling the prevention of complications so that it is included in one of the Healthy Indonesia Program with a Family Approach (PIS-PK/Program Indonesia Sehat dengan Pendekatan Keluarga) indicators. This research aims to determine the relationship between education level, economic status, and knowledge level with compliance in taking medication. This research was observational analytic with a cross-sectional approach. The respondents in this study were hypertension patients listed on PIS-PK in the Mijen District for the period January-August 2020, which included the inclusion and exclusion criteria of 45 respondents. Primary data were obtained using MMAS-8, HK-LS, and a hypertension management knowledge questionnaire. Technique sampling was used consecutively. Data analysis used the Spearman rank correlation test. In this research can be concluded education level (p= 0.025) with relation coefficient (r=0.334) and economic status (p=0.000) with relation coefficient (r=0.550), level of knowledge about hypertension (p=0.000) with relation coefficient (r = 0.545) and knowledge about hypertension management (p=0.005) with relation coefficient (r = 0.413). The higher level of education, the economic status, the level of knowledge its makes higher the compliance in taking medication for hypertension patients listed on the Healthy Indonesia Program with a Family Approach in the Mijen District.Keywords : Education, Economic, Knowledge, Compliance Correspondence : merry.tyas@unimus.ac.id